Desenvolvimento e aplicação do IBI em riachos de uma ria fluvial na Amazônia Oriental - COSTA, Luma Tainee Dias (2018)
The Index of Biotic Integrity (IBI) is one of the main tools to monitor the biota health nowadays and has been applied to several environments as well used different groups of organisms. Although there are numerous researches in the south of the Brazil, there is a scarcity related to this topic in the north, especially when related to the use of fish. By means of this study, the knowledge about the Amazon Forest can be extended, as well as the understanding of the aquatic environments of the region. The study aimed to create biological metrics, based on the fish communities sampled in the “drowned” streams inside of the Federal Conservation Unit, the Caxiuanã National Forest, in state of Pará, to evaluate the biotic integrity of the outside streams. To develop the work these methodological steps were followed which consist in the reference scenario composition, constituted by the streams inside of the National Forest; the metrics selection, which will compose of, the index, the score of these metrics and, lastly, the IBI calculation that results in classification of the streams outside of the National Forest in one of the integrity categories (good, fair, poor or very poor). We tested 95 attributes of the fish communities that cover different levels of organization, as composition, habitat use, hypoxia tolerance and trophic composition. Of these, only eleven attributes have been confirmed as effectively valid in demonstrating the effects of human activities on fish communities, which were used to calculate the IBI for the drowned streams exposed to the anthropic activities of the Eastern Amazon. Of the 17 streams sampled outside of the National Forest, two were classified as good; five as regular; three as poor; and six as very poor, according to the descriptors of biotic integrity. The results of this study complement and corroborate results already found by ecological studies about the ichthyofauna of Caxiuanã and its surroundings, region that is mainly affected by deforestation, where its aquatic communities already demonstrate the implications of these activities.